InterPACIFIC project: Comparison of invasive and non-invasive methods for seismic site characterization. Part I: Intra-comparison of surface wave methods. Issue 82 (March 2016) - Garofalo, F.; Foti, S.; Hollender, F.; Bard, P.Y.; Cornou, C.; Cox, B.R.; Ohrnberger, M.; Sicilia, D.; Asten, M.; Di Giulio, G.; Forbriger, T.; Guillier, B.; et al.
Abstract: The main scope of the InterPACIFIC (Inter comparison of methods for sitepar ameter and veloc ity profi lec haracterization) project is to assess the reliability of in-hole and surface-wave methods, used for estimating shear wave velocity. Three test-sites with different subsurface conditions were chosen: a soft soil, a stiff soil and a rock outcrop. This paper reports the surface-wave methods results. Specifically 14 teams of expert users analysed the same experimental surface-wave datasets, consisting of both passive and active data. Each team adopted their own strategy to retrieve the dispersion curve and the shear-wave velocity profile at each site. Despite different approaches, the dispersion curves are quite in agreement with each other. Conversely, the shear-wave velocity profiles show a certain variability that increases in correspondence of major stratigraphic interfaces. This larger variability is mainly due to non-uniqueness of the solution and lateral variability. As expected, the observed variability in V S, 30 estimates is small, as solution non-uniqueness plays a limited role. Highlights: Variability of surface wave analysis results are studied with a blind test. Three subsoil conditions are considered: soft soil, stiff soil, rock outcrop. Different methods are used to analyze active and passive data. A low variability is observed on the estimates of the experimental dispersion curve. Variability in VS profiles is due to parameterization and solution non-uniqueness.